1977
DOI: 10.1254/jjp.27.563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diltiazem on the Membrane Potential of Uterine Smooth Muscle

Abstract: On the other hand, methoxamine usually induced negative chronotropic and inotropic effects in both preparations, and these negative effects were not blocked by atropine, tetrodotoxin and phentolamine. These results suggest that phenylephrine produces a cholinergic excitation which may occur through an adrenergic alpha-mechanism in parasympathetic nerve terminals, in addition to its adrenergic beta-stimulating effect.In 1968, James et al.(1) reported that sinus deceleration with the adrenergic alpha stimulant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…In a similar study, negative, positive and combined chronotropic responses were observed but the specific effects did not appear to be dose related 14 . A study using isolated canine atrial and ventricular preparations also produced mixed chronotropic responses 15 . Others have shown that, through α 1 ‐adrenergic mediated reduction in acetylcholine release from parasympathetic neurons, phenylephrine reduces the magnitude of bradycardia produced by direct vagal stimulation 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, negative, positive and combined chronotropic responses were observed but the specific effects did not appear to be dose related 14 . A study using isolated canine atrial and ventricular preparations also produced mixed chronotropic responses 15 . Others have shown that, through α 1 ‐adrenergic mediated reduction in acetylcholine release from parasympathetic neurons, phenylephrine reduces the magnitude of bradycardia produced by direct vagal stimulation 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that epinephrine induced ACh release by cardiac parasympathetic efferent postganglionic neurons is supported by findings that ACh liberation from parasympathetic cardiac nerve fibers is facilitated by α 1 -adrenoceptors (Chiba 1977;Flavahan and McGrath 1982;Bognar et al 1990). However, vagal efferent postganglionic axon terminals are not equipped with α 1 -or α 2 -adrenoceptors (Manabe et al 1991).…”
Section: Discussionmentioning
confidence: 94%
“…However, Mukherjee et al (8) found more 13-adrenoceptors and fewer «-1 adrenoceptor binding sites in the dog myocardium than rabbit or rat heart. Furthermore, Chiba [9] and Endoh et al [10] reported that adrenoceptors mediating positive chronotropic and inotropic responses in the dog heart were ]3-adrenoceptors not post-synaptic ct-adrenoceptors.…”
Section: Discussionmentioning
confidence: 99%
“…They found more 13-adrenoceptor and fewer post-synaptic c~-1 adrenoceptor binding sites in the dog myocardium. Moreover, functional observations in the isolated dog heart preparations showed that positive cardiac effects of sympathomimetic amines were mostly mediated by 13-adrenoceptors [9,10]. Etilefrine has been postulated as a cardioselective 13-adrenoceptor or 13-1 adrenoceptor agonist [4,11].…”
Section: Introductionmentioning
confidence: 99%